Risk factors of preeclampsia and eclampsia in Sanglah General Hospital from March 2016 to March 2017 - Ng Teng Fung Vincent; I Made Darmayasa; Anom Suardika (DiscoverSys Inc., 2018)
Background: Preeclampsia and eclampsia have been increasing at an alarming rate. It is a challenging task for doctors and pregnant mothers. Preeclampsia defined as new onset of hypertension (≥140mmHg systolic or ≥90mm Hg diastolic on at least two occasions 6 hours apart) and proteinuria (at least 1+ on dipstick or ≥300mg in a 24-hour urine collection) after 20 weeks of gestation. Eclampsia defined as neurologic involvement in the form of generalized tonic-clonic convulsions in women with preeclampsia is termed eclampsia if the seizures cannot be attributed to any other cause such as epilepsy, cerebral infection, tumor or ruptured aneurysm. Aim: This study aims to find the association of risk factors for preeclampsia and eclampsia. The risk factors for preeclampsia and eclampsia are obesity, primigravida, multiple pregnancies, diabetes, pre-existing hypertension, family history, expecting mother’s age, nutritional status, and socioeconomic status. The study was carried out by using descriptive research and data were collected from medical records in Sanglah hospital which has 140 cases. Results: The results for preeclampsia are highest in expecting the age of 20-35 years old, primigravida women with gestational age > 37 weeks, overweight and overnourished women, a middle socioeconomic status and also without risk factors. The results for eclampsia are dominant in expecting age of 20-35 years old, primigravida women with gestational age > 37 weeks, women with middle socioeconomic status and majority without risk factors, and women who are overweight and overnourished. Conclusion: Preeclampsia and eclampsia cases are highest in expecting age of 20-35 years old, primigravida women with gestational age >37 weeks, overweight and overnourished women, majority women without risk factors and from middle socioeconomic status.